Qualitative evaluation of extracts macerated with different solvents for extraction of glycoalkaloids and flavonoids from Dioscórea bulbifera in standard conditions obtained in the eastern plains of Colombia (2020)
Different solvents were qualitatively evaluated for the extraction of steroid nuclei and flavonoids in Dioscorea bulbifera Salv. bulbs. The raw bulb was analyzed and macerated in water, oil, and 40% alcohol. The triangulation of the observations in the RxSh and RxL-B with a defined chemical pattern, a target, and the experimental test evaluated the presence of the chemical nucleus. The relationship matrix analyzed that the alcohol had a higher affinity to flavonoid and alkaloid compounds, detecting that 100% of the tests carried out were positive for each nucleus. Alkaloid compounds were detected in 83% in raw bulb samples and more than 70% for flavonoids. Mineral oil contains preservative characteristics of the bulb and negative results for both nuclei. It is concluded that the bulbous alcoholate of D. bulbifera extracts compounds from flavonoid nuclei and steroids to be used as a bioactive ingredient for application in different industrial areas.